The Influence of Leadership Style, Communication Style on Nurse Performance With Control System as an Intervening Variable Hospital - Mas Andika Cakra Purnama; CSP Wekadigunawan; Hasyim Hasyim (Jurnal Health Sains, 2023)
The performance of nurses is an important aspect in hospitals because it is an indicator of the quality of health services. Nurses as human resources in carrying out health services in hospitals are an important resource and are needed to achieve optimal performance. Improving the performance of nurses will increase the effectiveness and productivity of the hospital. Therefore, to achieve good performance, leadership and communication styles are also needed. The purpose of this study was to determine the leadership style and communication with the control system as an effort to assess the performance of nurses. This research is a cross-sectional research design. Data collection was carried out at the Inpatient Unit of RS X Tangerang in June-July 2020 with a total sample of 77 people as research samples. The results there was no influence between the leadership style on the nurse's performance; the leadership style on the control system; communication on the nurse's performance; between the leadership style and communication on the nurse's performance with the system control as mediation. However, there was an influence between communication on the control system and the control system on the nurse's performance.